A Polyamine-Based Dinitro-Naphthalimide Conjugate as Substrates for Polyamine Transporters Preferentially Accumulates in Cancer Cells and Minimizes Side Effects in vitro and in vivo - Ma, Jing; Li, Yingguang; Li, Linrong; Yue, Kexin; Liu, Hanfang; Wang, Jiajia; Xi, Zhuoqing; Shi, Man; Zhao, Sihan; Ma, Qi; Liu, Sitong; Guo, Shudi; et al. (Frontiers in Chemistry, 2020)
A new class of polyamine-based naphthalimide conjugates 5a-5c, 7a-7b and 11a-11b with and without alkylation modified were synthesized and the mechanism was determined. Compared with amonafide, dinitro-naphthalimide conjugate 5c with a 4,3-cyclopropyl motif displayed better cell selectivity between cancerous and normal liver cells in vitro and in vivo. More importantly, 5c at the dosage of 3 mg/kg (57.97%) displays better anti-tumor effects with the positive control amonafide (53.27%) at 5 mg/kg in vivo. And a remarkably elevated antitumor activity and a deduced toxicity were also observed for 5c at 5 mg/kg (65.90%). The up-regulated p53 and the apoptotic cells (73.50%) indicated the mechanism of 5c to induce apoptosis may result from its enhanced DNA damage. The further molecular mechanism indicated that in addition to targeting nuclear DNA, 5c can modulate the polyamine metabolism by up-regulating PAO in a different way from that of amonafide. And also by targeting PTs overexpressed in most of cancer cells, 5c down-regulates the concentrations of Put, Spd and Spm, which are in favor of suppressing fast-growing tumor cells. Our study implies a promising strategy for the design of naphthalimide conjugates to treat hepatic carcinoma with notable activities and deduced toxicities at a low dosage.